1999
DOI: 10.1096/fasebj.13.13.1817
|View full text |Cite
|
Sign up to set email alerts
|

L‐arginine increases UVA cytotoxicity in irradiated human keratinocyte cell line: potential role of nitric oxide

Abstract: Human fibroblasts and keratinocytes possess nitric oxide synthases (NOS), which metabolize L-arginine (L-Arg) for producing nitric oxide (NO*). This report delineates the relations between NO* and UVA in the human keratinocyte cell line HaCaT. NOS activity was stimulated by exposure of cells to L-Arg just after irradiation. L-Arg (5 mM) supply led to an increase in UVA (25.3 J/cm(2)) cytotoxicity (% of viability 18 +/- 3%) whereas neither L-Arg itself nor UVA irradiation induced cell death at the doses used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Since then, the interactions between SODs and ROS are being re-evaluated [85]. For example, exogenous SOD and L-thiocitrulline (an inhibitor of nitric oxide synthesis) prevented this cytotoxic effect, suggesting that the ratio of nitric oxide to superoxide radicals is important in UV-A-induced cytotoxicity [150]. Additionally, exogenous Cu-Zn SOD reduced the cell membrane injuries in UVB-irradiated murine fibroblast cells [151].…”
Section: Superoxide Dismutases (Sods)mentioning
confidence: 99%
“…Since then, the interactions between SODs and ROS are being re-evaluated [85]. For example, exogenous SOD and L-thiocitrulline (an inhibitor of nitric oxide synthesis) prevented this cytotoxic effect, suggesting that the ratio of nitric oxide to superoxide radicals is important in UV-A-induced cytotoxicity [150]. Additionally, exogenous Cu-Zn SOD reduced the cell membrane injuries in UVB-irradiated murine fibroblast cells [151].…”
Section: Superoxide Dismutases (Sods)mentioning
confidence: 99%
“…whether caspase activation, PARP activity, and/or p38 MAP kinase activation are required for NO-induced death of NPC, we pretreated cells with a cell-permeant caspase inhibitor (zVAD-fmk), an inhibitor of PARP (3-aminobenzamide) (56,57), or an inhibitor of p38 MAP kinase (SB 203580) (58). Preliminary studies showed that none of the three inhibitors affected cell viability under basal culture conditions (data not shown).…”
Section: Activation Of Parp Caspases and P38 Map Kinase Are Each Rementioning
confidence: 99%
“…UVA can also cause the production of reactive nitrogen species (e.g. nitric acid and peroxynitrite), which can cause cellular and DNA damage [8]. UVA predominantly induces oxidation of purines and of relatively few pyrimidines, as well as a few (single-)strand breaks in DNA [9][10][11].…”
Section: Dna Damagementioning
confidence: 99%